Organizational justice, opportunism, governance costs and relationship performance: A study in family farming cooperatives (Desenvolvimento em Questão, 2026)
This study investigates the relationship between organizational justice, opportunism, governance costs, and relationship performance within an agricultural cooperative composed of family farming members. A quantitative research design was adopted, and data were collected through a structured questionnaire administered to cooperative members between August and November 2024. The data were analyzed using descriptive statistics. The results indicate predominantly positive perceptions of organizational justice, particularly in the interactional dimension, highlighting respectful treatment and effective communication by the cooperative’s management. Distributive justice was also positively evaluated, although variations were observed regarding the criteria used for distribution. Procedural justice revealed opportunities for improvement, especially in decision-making processes. With respect to opportunism, strong opportunistic behavior was perceived at low levels, though some respondents reported information withholding. Weak opportunism, associated with insufficient support among members, presented a moderate level of perception. Governance costs were assessed as moderate, with greater variability identified in conflict resolution. Overall, relationship performance was highly rated, reinforcing collaboration and mutual support among cooperative members.
Keywords: Opportunism; Organizational Justice; Relationship Performance; Governance Costs; Family Farming